THE INFLUENCE OF NONLINEAR AND LINEAR DEFECTS ON THE LIGHT PROPAGATION THROUGH LINEAR ONE-DIMENSIONAL PHOTONIC LATTICE - Kuzmanović, Slavica; Stojanović Krasić, Marija; Mančić, Ana; Drljača, Branko; Stepić, Milutin (Bulletin of Natural Sciences Research, 2016)
In this paper, the light beam propagation through one-dimensional photonic lattice, possessing one nonlinear defect and one linear defect, has been investigated numerically. Different dynamical regimes have been identified in terms of the distance between the two defects, position of the incident light beam, the width of linear defect, the values of nonlinearity and presence of the transverse kick. Strong localized modes on the defects, breathing and zig-zag modes in the area between defects have been observed. It has been concluded that the width of the linear defect placed next to the nonlinear one influences localization of the beam at the nonlinear waveguide. On the other hand, the nonlinear defect, regardless of the values of nonlinearity, have a small influence on the beam propagation in photonic lattice. It has been observed that the transverse kick of the initial beam leads to the distortion of localized structures. By launching the light beam towards defects, the reflection of light has been noticed. Presented results can be useful for different applications, such as blocking, filtering and routing of light beam through optical media.